The international law of state responsibility : an introduction - Kolb, Robert, 1967- (Principles of international law, 2017)
This highly readable book examines the law of State responsibility, presenting it as a fundamental aspect of public international law. Covering the key aspects of the topic, it combines a clear overview with use of specific case studies in order to provide a deeper understanding. The concise chapters are organized into two parts. Part One provides a structural overview of the law, with up-to-date coverage of practice and case law reflecting the key international law reports. Part Two offers specific case studies, asking probing questions in order to explore how the international legal order deals with breaches of its norms and what rights and faculties are accorded to the aggrieved State. With an approach that is legally analytical yet also practical, this accessible book will provide valuable insights to both scholars and practitioners of international law. Its clear structure and guidance on the latest practice and case law will also make it an ideal choice for students.